OPTIMALISASI PENYIDIKAN TINDAK PIDANA PENAMBANGAN EMAS TANPA IZIN OLEH PENYIDIK SATUAN RESKRIM DI WILAYAH HUKUM POLRES SOLOK SELATAN - Ricky Ricardo, Fitra Oktoriny , (Normative Jurnal Ilmiah Hukum, 2022)
Mining without permits is rife in almost every region that has the potential to be rich in minerals. The Unlicensed Gold Mining activities are mining businesses carried out by individuals, groups of people or companies/foundations with legal entities. In its operation, it does not have a permit from a central or regional government agency in accordance with the provisions of the applicable laws and regulations. This phenomenon is interesting for researchers to be used as a research study. The results of the research conducted, it was found that the performance of investigators from the Criminal Investigation Unit of the South Solok Police in handling the Unlicensed Gold Mining case was felt to be not optimal. Factors that influence the performance of investigators in handling cases of Unlicensed Gold Mining in the South Solok Police area, include internal factors and external factors. Internal factors, due to the minimum number of personnel and inadequate human resources from investigators and limited facilities and infrastructure. While external factors, due to the lack of welfare of the people of Solok Selatan Regency and the lack of knowledge and awareness of the community towards the law. Efforts to further maximize the improvement of investigator performance can be carried out by maximizing training, vocational education, increasing harmonization, empowering, optimizing existing personnel, facilities and infrastructure, increasing coordination internally and externally as well as carrying out close monitoring and control of investigators at every stage. investigation.